Integration of 21st Century Skills in Economics Learning and Its Impact on Learning Outcomes: A Global Bibliometric Analysis (2015–2025) - Permanik, Jilan Azizah Dwi; Lakilaki, Eogenie; Eprilia, Winda (Lembaga Bale Literasi, 2026)
This study aims to map the development of research on the integration of 21st-century skills into economics learning and its relationship to learning outcomes through a bibliometric approach. The research background is based on the increasing global need for 21st-century competencies, but the literature shows that their application in the context of economics education is still limited and unstructured. Analysis was conducted on 467 international publications, which were then selected to 180 relevant articles based on title and abstract. All data were analyzed using R Studio with the Bibliometrix package for the period 2015–2025 to produce visualizations related to publication trends, author and country collaborations, keyword co-occurrence, and thematic structure. The results show a significant increase in the number of publications post-2020, the dominance of general themes such as critical thinking and digital literacy, and minimal direct links to economics learning. Collaboration patterns remain regional and have not yet formed a global network, while thematic map analysis reveals that economics education has not yet entered the main cluster of 21st-century skills research. These findings emphasize the existence of a disciplinary gap that needs to be bridged through further research, particularly to strengthen the position of economics education in the global literature map. This research provides an important contribution as a basis for developing future research directions that are more integrated and contextual.